PENGEMBANGAN LEMBAR KERJA SISWA HIGHER ORDER THINKING SKILLS (HOTS) PADA MATERI MOMENTUM, IMPULS DAN TUMBUKAN SMA KELAS XI/SEMESTER 1 - Khasyyatillah, Isra; Irianti, Mitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research aimed to develop higher order thinking skills (HOTS) workheet in momentum, impulse, and collision for senior high school grade xi/semester 1. Research conducted at the laboratory of physiscs learning strategy development. this type of research is Reseach and Development (R&D) with 4D model development, the procedure includes define, design, develop and disseminate. This research was carried out until develo. Data collection instruments used validation sheets for 5 validator, included 3 lecturer and 2 teacher. Aspects assessed include graphic and presentation, language, and the contents of higher order thinking skills (HOTS) workheet. Based on the result of data analysis showed that all aspects got average score in the range of 3.4 to 4 categories of high and very high. Thus, higher order thinking skills (HOTS) workheet was valid.Key Word: Higher Order Thinking Skills worksheet, HOTS, Worksheet, Momentum,impulse and collision worksheet.